Put yourself in the literary work: a Reading of those who are on the border - Almeida, Ísis Lopes de (2020)
In this paper, we developed the idea that the hermeneutic philosophy contemplates a moral attitude of empathy, of putting yourself in the other’s spot, through the literary text. From this perspective, we discussed the oppressive situation of two fictional characters – Popróshin, from “Diário de um louco”, story by Nikolai Gógol, and the madman from Cati, from the same title by Dyonelio Machado. The presented human beings in these works are driven into madness by oppressive unfair and violent social realities that touch the reader. We consider that, bowing down on human nature questions, the hermeneutic points to other possibilities that the being has to exists and allows the interpreter an opportunity to exchange oneself in the construction of understanding, increasing its horizons of meanings. Such an interpretative point of view requires the reader to put himself in the work in order to hear it, once what is researched is not separate from the researcher. Thus, as theoretical basis, we based ourselves on the assumptions of hermeneutic philosophy, especially with Hans-Georg Gadamer and Ernildo Stein, on the ideas concerning the theme of translation by Jacques Derrida, and authors who can contribute to a reflection of violence and of madness.